The Correlation of Adsorption Behavior between Ciprofloxacin Hydrochloride and the Active Sites of Fe-doped MCM-41 - Wu, Ying; Tang, Yiming; Li, Laisheng; Liu, Peihong; Li, Xukai; Chen, Weirui; Xue, Ying (Frontiers in Chemistry, 2018)
Fe-MCM-41s with various molar ratios of silicon to iron (20, 40, 80 and 160) were prepared to investigate adsorption properties of ciprofloxacin hydrochloride (CPX) in aqueous solutions. Fe-MCM-41s were characterized by transmission electron microscope (TEM), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), nitrogen adsorption/desorption isotherms and infrared spectroscopy (FT-IR). Effects of silicon–iron ratio, adsorbent dosage, pH and temperature were conducted to explore the adsorption mechanism of CPX on Fe-MCM-41. The results showed that the introduction of iron facilitated the absorption quantity for CPX from 20.04 to 83.33 mg g-1 at 120 min of reaction time, which was mainly attributed to surface complexation. The promotion of hydrophobic effect, electrostatic interactions and π-π electron donor–acceptor interaction also played coordinate roles in the adsorption process. The experimental kinetic data followed both the pseudo-second-order and intra-particle diffusion models, while the adsorption isotherm data fit well to Freundlich model at high temperature. Thermodynamic study showed that the adsorption was spontaneous. Under the effect of electrostatic interaction, pH of the solution strongly affected CPX adsorption. Five representative metal cations (Ca, Cu, Ni, Pb and Cd) were chosen to study the effects on CPX adsorption and their complexation. The inhibiting effect of metal cations on CPX adsorption was sequenced in the order of Cu > Ni > Pb > Cd > Ca, which followed the same order as the complexation stability constants between CPX and cations. The Fe-MCM-41 adsorbent possessed excellent reusability for 4 cycles use, suggesting a potential applicability of Fe-MCM-41 to remove CPX in water.